Wildlife-vehicle collisions in Khao Yai National Park, Thailand: Impact on native species for some conservation management - Nattaphat Rattanawanawong; Naris Bhumpakphan; Utis Kutintar; Ronglarp Sukmasuang (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Rattanawanawong N, Bhumpakphan N, Kutintara U, Sukmasuang R. 2022. Wildlife-vehicle collisions in Khao Yai National Park, Thailand: Impact on native species for some conservation management. Biodiversitas 23: 3050-3061. Wildlife-vehicle collisions (WVCs) remain a major challenge in wildlife management worldwide, especially in conservation areas with transport routes passing through. This study was operated along a 48 km long highway, which conducted 207 surveys in a natural world heritage site from February 2018 to January 2019. A total of 391 wild animal carcasses were found in 90 species. The carcasses found, according to the taxonomic group, were reptiles (67.52%), followed by mammals (14.83%), amphibians (4.35%), birds (3.32%). Reptiles were most affected by road use, especially tortoises in Family Geoemydidae and Family Testudinidae that two critically endangered species were found. This study found that members of Family Colubridae were most affected that 26 species, a total of 144 animal carcasses were found, accounting for 29.15% of the number of all carcasses. The most affected species were forest garden lizard (Calotes emma) in the Family Agamidae, where 99 carcasses were found, accounting for 25.31% of the total. In March showed the highest number of the carcasses, followed by April. All of the carcasses found in the evening slightly more than the morning indicated that wild animals died more during the day than at night. The number of vehicles day-1 significantly affected wildlife mortality per day. Reducing the number of vehicles per day-1 entering and reducing vehicle speed, including the number of tourists, as well as banning travel at night, would mitigate the problem. Further, educational signage about wildlife diversity and the risk of road mortality should be installed at the park to remind visitors about the unique fauna in the national park and emphasize the importance of conservation.